The Impact of a Mnemonic Acronym on Learning and Performing a Procedural Task and Its Resilience Toward Interruptions - Radović, Tara; Manzey, Dietrich (Frontiers in Psychology, 2019)
The present study examines the potential impact of a mnemonic acronym on the learning, the execution, the resilience toward interruptions, and the mental representation of an eight-step procedural task with sequential constraints. 65 participants were required to learn a sequential task, including eight different steps which had to be carried out in a predefined sequence. 33 participants were provided with the acronym “WORTKLAU” as a mnemonic to support the learning and execution of the task and the other 32 participants had to learn and execute the task without such support. Each letter of the acronym coded one step of the task, involving a binary decision about a certain property of the complex stimulus. In 60 out of 72 trials of the task, participants were interrupted between different steps, and had to perform a 2-back interruption task for 6 or 30 s, after which they had to resume the procedural task as quickly as possible at the correct step. Learning times, performance in uninterrupted trials, and post-interruption performance measures were analyzed. Results of Experiment 1 suggest that the mnemonic acronym enhanced learning of the task sequence, and provide some evidence for a hierarchical mental representation of the task, resulting in faster resumption times at certain steps of the procedure after an interruption. In Experiment 2 the internal structure of the acronym was even emphasized by a hyphen at the borders of the two words included in the acronym (WORT-KLAU). This improved the resilience toward interruptions at the border step of the procedure significantly. Our results provide evidence for beneficial effects of mnemonic acronym particularly for the learning of a sequential procedural task. In addition, they suggest that the structure of mnemonic acronym directly impacts the mental representation of a task. Finally, they show that mnemonic acronyms could be used to improve the resilience toward detrimental effect of interruptions, at least at certain task steps of a procedural task.